Effects of Combined Prenatal Yoga and Structured Pregnancy Exercise on Serum Cortisol Regulation and Active-Phase Labor Duration - Elok Dewi; Emi Wulandari (Journal of Research in Midwifery and Healthcare, 2026)
Prenatal stress and prolonged labor are important concerns in maternal health because they may affect maternal comfort, labor progression, and the need for obstetric intervention. Prenatal yoga combined with structured pregnancy exercise has been proposed as a non-pharmacological strategy to support stress regulation and physiological readiness for childbirth. This quasi-experimental study involved 26 third-trimester primigravida women from maternity clinics in Nganjuk Regency, Indonesia, with 13 participants in the intervention group and 13 participants in the control group. Participants in the intervention group received combined prenatal yoga and structured pregnancy exercise twice weekly for three weeks, whereas the control group received structured pregnancy exercise only with the same frequency and duration. Serum cortisol levels were measured before and after the intervention using ELISA. The active phase of first-stage labor was defined as the period from 4 cm cervical dilation to full dilation and was documented using a partograph by attending midwives. The intervention group showed a significantly greater mean reduction in serum cortisol than the control group (−209.67 ± 56.30 vs. −129.96 ± 186.93 ng/ml; p = 0.010, Mann-Whitney U) and a shorter active-phase labor duration (4.08 ± 1.29 vs. 5.54 ± 0.90 hours; p = 0.003, independent t-test). A significant reduction in cortisol was also observed within each group (intervention: p < 0.001, paired t-test; control: p = 0.001, Wilcoxon test). These findings indicate that combined prenatal yoga and structured pregnancy exercise was associated with improved serum cortisol regulation and shorter active-phase labor duration compared with structured pregnancy exercise alone. Delivery mode was not evaluated as an outcome; therefore, further studies are needed to assess whether this intervention influences cesarean section rates.